Low-dose ferric carboxymaltose vs. oral iron for improving hemoglobin levels in postpartum East Asian women: A randomized controlled trial - Takeshi Nagao; Ken Takahashi; Sho Takahashi; Ryo Yokomizo; Osamu Samura; Aikou Okamoto (PLoS ONE, 2025)
Ferric carboxymaltose (FCM) is widely used to correct anemia and replenish iron stores rapidly, particularly in Western populations. However, lower doses of FCM are typically used in East Asia, with limited research on their effectiveness, especially in postpartum women. This randomized controlled trial aimed to assess the efficacy of low-dose FCM compared with oral ferrous sulfate in increasing postpartum hemoglobin (Hb) levels and replenishing iron stores in East Asian women. Sixty postpartum women with Hb levels < 10 g/dL and serum ferritin ≤ 30 ng/mL were randomized to receive either intravenous FCM (500 mg at baseline and 2 weeks) or oral ferrous sulfate (210 mg daily for 4 weeks). The primary outcome was the increase in Hb levels at 2 weeks post-enrollment. Secondary outcomes included serum ferritin, transferrin saturation, the Edinburgh Postnatal Depression Scale (EPDS) score, and adverse events at 4 weeks. The FCM group demonstrated a significantly greater increase in Hb levels at 2 weeks (mean difference 0.42 g/dL; 95% CI: 0.12–0.72; P =  0.006), with markedly higher ferritin (adjusted mean difference 356.0 ng/mL; 95% CI: 321.0–403.0; P <  0.001) and transferrin saturation (adjusted mean difference 10.76%; 95% CI: 4.20–17.31; P =  0.002) at 4 weeks. Although there was no significant difference in final Hb levels at 4 weeks (mean difference 0.36 g/dL; 95% CI: -0.01–0.72; P =  0.055), the FCM group had a lower median EPDS score (median difference -3.0; 95% CI: -5.0 to -1.0; P =  0.002) and fewer gastrointestinal side effects, including constipation and nausea. Hypophosphatemia occurred asymptomatically in three patients in the FCM group. These findings suggest that low-dose FCM infusion is highly effective in increasing Hb levels at 2 weeks post-enrollment, with fewer gastrointestinal side effects and higher ferritin levels observed at 4 weeks post-enrollment compared with oral ferrous sulfate. This study was registered at the UMIN Clinical Trials Registry, which meets the requirements of the ICMJE, on December 1, 2021 (ID: UMIN000046049).